Can pluripotent/multipotent stem cells reverse Parkinson’s disease progression? - Wu, Yongkang; Meng, Xiangtian; Cheng, Wai-Yin; Yan, Zhichao; Li, Keqin; Wang, Jian; Jiang, Tianfang; Zhou, Fei; Wong, Ka-Hing; Zhong, Chunlong; Dong, Yi; Gao, Shane (Frontiers in Neuroscience, 2024)
Parkinson's disease (PD) is a progressive neurodegenerative disorder characterized by continuous and selective degeneration or death of dopamine neurons in the midbrain, leading to dysfunction of the nigrostriatal neural circuits. Current clinical treatments for PD include drug treatment and surgery, which provide short-term relief of symptoms but are associated with many side effects and cannot reverse the progression of PD. Pluripotent/multipotent stem cells possess a self-renewal capacity and the potential to differentiate into dopaminergic neurons. Transplantation of pluripotent/multipotent stem cells or dopaminergic neurons derived from these cells is a promising strategy for the complete repair of damaged neural circuits in PD. This article reviews and summarizes the current preclinical/clinical treatments for PD, their efficacies, and the advantages/disadvantages of various stem cells, including pluripotent and multipotent stem cells, to provide a detailed overview of how these cells can be applied in the treatment of PD, as well as the challenges and bottlenecks that need to be overcome in future translational studies.